THE INFLUENCE OF HANDPHONES ON STUDENTS' LEARNING MOTIVATION OF MI HASYIM ASY'ARI PADI TALANGSUKO - Apriliani, Defina Dwi; Amala, Afdhirotul Isna; Pudiarti, Alya Arung; Akbar, Putri Wulan (JRCE (Journal of Research on Community Engagement), 2024)
In the era of digitalization, which is very fast, it has no small impact, the decline in the quality and level of student learning is one that is rife, caused by none other than cellphones. This research aims to find out how much influence mobile phones have on learning motivation at MI Hasyim Asy'ari Padi Talangsuko Malang Regency. This research method uses descriptive qualitative. The data collection technique was in the form of a survey via Google form containing questions about the use of cell phones associated with learning consistency. The data analysis used is data reduction, data presentation, conclusion/data verification. The results of the study show that students stated that the use of smartphones had a positive impact on respondents by 80%. This shows that the percentage of 80% is in the high category, and it can be said that students agree that the use of smartphones has a positive impact on the teaching and learning process.